(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In this thesis, an attempt has been made analytically as well as empirically to analyze and address the above IPv4IPv6 migration issues and carry out an in-depth investigation of the deployment and security issues of the next generation internet protocol IPv6. In the first chapter, an attempt has been made to throw light on introduction to IPv6 and Migration Techniques with the motivation for taking the topic. The chapter outlines the objectives of the research and also reports the contribution made by the author during the course of study. In the initial part of this research work, we examine the reasons for migrating to IPv6.The migration involves challenges (both technical and non technical) which need to be addressed. We also establish guidelines or benchmarks for IP migration. For seamless integration and co-existence between the two non-homogeneous protocols, the migration techniques need to be optimized and correctly deployed so that internet downtime doesn’t occur which may lead to performance and QoS degradation. In this research work, we have empirically carried out implementation of existing migration techniques using OPNET Modeller Simulation. Based on the calculated parameters, an approach has been made towards finding better technique among the existing migration techniques. The experiment helps us in solving the problem of choosing best IPv6 migration technique. Talking about the migration from IPv4 to IPv6, one thing that automatically comes to our mind is the security aspects of the internet migration. The security of the previous version of IP i.e. IPv4 has been tested over the years, but in case of IPv6, we are still naive about the security vulnerabilities.